2011
DOI: 10.4236/jbise.2011.46054
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years study of solar, geomagnetic, cosmic ray activity links with monthly deaths number (n-850304)

Abstract: The interrelationship between human life and death at the end of the XX and beginning of the XXI centuries is the topic of this study. The aim of the study is to study links between time, Solar (SA), Geomagnetic (GMA) and Cosmic Ray (CRA) (Neutron) activity and monthly deaths distribution from all and six subgroups of death causes in years 1990-2009 for ad-ditional clarification of the role of exogenic factors in human homeostasis. Methods and patients: 850304 deaths (44657 men, 400647 woman) and 6 subgroups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…In a number of following observations also significant links were seen for total number of AMI and its different subtypes (STEMI, NSTEMI, Q-wave and non-Q-wave AMI) [21,35]. Similar findings were published for great groups of cerebral stroke (CVA) [16]. Recent studies confirmed that more than 75% of AMI are a result of atheroma fissuring and/or rupture [37][38][39] and strong links connect timing of these events with high CRA (neutron activity).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In a number of following observations also significant links were seen for total number of AMI and its different subtypes (STEMI, NSTEMI, Q-wave and non-Q-wave AMI) [21,35]. Similar findings were published for great groups of cerebral stroke (CVA) [16]. Recent studies confirmed that more than 75% of AMI are a result of atheroma fissuring and/or rupture [37][38][39] and strong links connect timing of these events with high CRA (neutron activity).…”
Section: Discussionsupporting
confidence: 67%
“…At the same time artificial magnetic fields found their place in severe depression treatment [46,47]. Physical factors' involvement in central nervous system, eye and other human organs functions can be linked with timing of traffic accidents and trauma, as it was seen in previous studies, comparing four levels of GMA [16,23,40], and in this study, concentrating on days with "Zero" GMA level. The presented data demonstrated the possible effects of high CRA (neutron activity) on a number of human pathologies, and mortality in general.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Melnikov et al (2010) reported significant influence of solar activity (solar spots and the intensity of solar radiation with a wavelength of 10.7 cm) on diastolic blood pressure. On the other hand, Stoupel et al (2011) demonstrated, based on the analysis of deaths of 850,000 people in 20 years, that cosmic ray (especially neutrons) and sunny radiation (mostly protons and electrons) have the greatest impact on monthly deaths distribution. Parallel changes in atmospheric and intracranial pressures are not necessarily indicative of their mutual dependence but can be evidence of the existence of an external factor.…”
Section: Discussionmentioning
confidence: 98%